Analysis of Drug Management at the Pharmacy Installation of Thursina Duri Hospital, Mandau District in 2024: Analysis of Drug Management at the Pharmacy Installation of Thursina Duri Hospital, Mandau District in 2024 - Candra, Leon; Faizah, Hasifah (Badnur Medisa Group, 2025)
Administering medication in hospitals is an important aspect of hospital services. Medication management in hospitals is an important aspect of hospital management. The aim of good drug management in a hospital is so that the drugs needed are available at all times, in sufficient and guaranteed quantities to support quality services. Medicine is an important element for healing efforts and hospital operations. The aim of this research is to determine drug management in the Thursina Duri Hospital Pharmacy Installation, Mandau District in 2024. This research uses qualitative research. The subjects of this research were 3 people. Data collection techniques use observation, interviews and documentation methods. The results of the research found obstacles in drug management, namely that the drug planning process still did not meet pharmaceutical standards because drug shortages were still found. The procurement process is carried out by purchasing directly from the distributor via letter order, however problems in procurement usually occur due to shortages of drugs at the distributor. The drug storage process meets pharmaceutical standards. The drug distribution process still does not use the UDD (Unit Dose Dispensing) system. The results of the research found obstacles in drug management, namely that the drug planning process still did not meet pharmaceutical standards because drug shortages were still found. The procurement process is carried out by purchasing directly from the distributor via letter order, however problems in procurement usually occur due to shortages of drugs at the distributor. The drug storage process meets pharmaceutical standards. The drug distribution process still does not use the UDD (Unit Dose Dispensing) system.